The Effect of Islamic Religious Education Teachers on Improving Student Behaviour and Personality at SMP Muhammadiyah 8 Surakarta - Aulia Nur Aini; Mohammad Zakki Azani (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
The influence of Islamic religion teachers in changing the behaviour and personality of students at SMP Muhammadiyah 8 Surakarta and the efforts of Islamic religion teachers as a means of motivation, directing, analysing. Responsible for shaping the character, knowledge, faith and commitment of students. Islamic Religious Education (PAI) should be used as a means to teach noble morals to children by placing Islamic Religious Teachers (PAI) as teachers and providing appropriate methods and media related to Islamic religion. Factors that help and hinder student character building at SMP Muhammadiyah 8 Surakarta come from teachers, parents, peers, and the environment in the community.